Modeling and optimal operation of carbon capture from the air driven by intermittent and volatile wind power. (1st July 2015) - Li, Canbing; Shi, Haiqing; Cao, Yijia; Kuang, Yonghong; Zhang, Yongjun; Gao, Dan; Sun, Liang
Abstract: CO2 capture from ambient air can compensate for all CO2 emissions to the atmosphere, ultimately reducing CO2 concentrations on a global scale. It has been widely explored. However, additional CO2 emits when CO2 -intensive fossil fuels are used to drive the systems of CO2 capture from air. A replacement of conventional energy by wind energy to power existing systems of CO2 capture from air is proposed in this paper and its technical feasibility is validated. The intermittency and volatility of wind power supply in seasonal variations are considered when wind power is used to meet the energy requirements for CO2 capture. Energy requirements for each device in the system of CO2 capture from air are specified and the characteristics of all devices are also analyzed. In order to investigate how flexible CO2 capture regarding the variations in wind power supply, an optimal operation model is established. Each device in the system of CO2 capture is considered as a separate load, thus devices are dispatched separately rather than as a whole to improve the acceptance of fluctuant wind power. The results demonstrate the feasibility of using intermittent and volatile wind power to capture CO2 from air. Highlights: Wind power-driven system of CO2 capture from air is discovered technically feasible. Devices are dispatched separately not as a whole because of intermittent wind power. Optimized dispatch reduces wind power curtailment and batteries workload.